LANGUAGE BELIEFS AMONG ADULT LEARNERS: INDIVIDUAL DIFFERENCES - Johari, Aiza (International Journal of Education, 2017)
To develop the quality of language learning and utilise learning opportunities in and out of a classroom, it is vital to understand individual's beliefs in language learning. White (2008) affirmed that an individual’s belief plays a key role in the learning process and language acquisition, especially the beliefs the learners have about themselves, language and language learning, and about the settings in which they contribute as language learners and users. This study identifies the English language learning beliefs of adult learners (between 45-50 years of age) in a local university in Sarawak. Questionnaire was the instrument to collect the data and the data were analysed using SPSS Version 21. The study showed that these adult learners have various levels of language beliefs. The results obtained can be used to enhance the teaching and learning of English language where language instructors can learn more about their learners and the learners’ language beliefs can further enhance learning process in the classroom.